Answer; 1/4 × 1/6
Step-by-step explanation: To turn a fraction division sentence into a multiplication sentence, simply multiply the second fraction by its reciprocal. For example 1/4 ÷ 6/1 is equaled to 1/4 × 1/6.
I hope this helps! please vote brainliest if so
The true statements about the equation y = 1.4x are
- (a) The equation represents a proportional relationship
- (b) The unit rate of y with respects to x is 1.4
- (d) A change of 2 units in x results in a change of 2.8 units in y
<h3>What are linear equations?</h3>
Linear equations are equations that have constant average rates of change. Note that the constant average rates of change can also be regarded as the slope or the gradient
<h3>How to determine the true statements?</h3>
The equation is given as:
y = 1.4x
The above equation is a proportional linear equation.
This is so because proportional linear equations are represented as;
y = mx
Where m represents the unit rate of change
So, we have:
m = 1.4
Rewrite as:
m = 14/10
Simplify
m = 7/5
When x = 2, we have:
y = 1.4 * 2
Evaluate
y = 2.8
Hence, the true statements about the equation y = 1.4x are (a), (b) and (d)
Read more about linear equations at:
brainly.com/question/14323743
#SPJ1
Answer:
In order to understand exponential equations with a whole number and a fraction, we have to revisit the definition.
Exponentiation is just repeated multiplication. For instance, if we have 2^3, we can see that 2 * 2 * 2 = 8. The number keeps getting bigger.
Likewise, if we have (1/2)^3, 1/2 * 1/2 * 1/2 = 1/8. The number keeps getting smaller. Notice a pattern?
When we have a number greater than 1 as a base in an exponential function, the number keeps growing. This is called exponential growth.
In contrast, whenever we have a number less than 1 as a base (i.e. a fraction), the number keeps getting smaller. This is called exponential decay.
Hope this helps.
Answer:
p = 8
Step-by-step explanation:
The n th term of an AP is
= a₁ + (n - 1)d
where a₁ is the first term and d the common difference
Given a₉ = 4 + 5p and d = 5, then
a₁ + 8d = 4 + 5p, that is
a₁ + 8(5) = 4 + 5p
a₁ + 40 = 4 + 5p ( subtract 40 from both sides )
a₁ = 5p - 36
a₂ = 5p - 36 + 5 = 5p - 31
a₃ = 5p - 31 + 5 = 5p - 26
a₄ = 5p - 26 + 5 = 5p - 21
Given that the sum of the first 4 terms = 7p - 10, then
5p - 36 + 5p - 31 + 5p - 26 + 5p - 21 = 7p - 10, that is
20p - 114 = 7p - 10 ( subtract 7p from both sides )
13p - 114 = - 10 ( add 114 to both sides )
13p = 104 ( divide both sides by 13 )
p = 8